2016
DOI: 10.1111/jicd.12206
|View full text |Cite
|
Sign up to set email alerts
|

Association between self‐reported and clinical oral health status in Belarusian adults

Abstract: Self-perceived oral health was significantly associated with clinical oral health status in this study. Self-reporting methods could be useful for population-based oral health surveys in Belarus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 22 publications
5
35
3
4
Order By: Relevance
“…Age, household income, dentures, the number of lost teeth, self-esteem, quality of life, stress level, sense of belonging, and level of depression are reportedly related to subjective OHS [32]. Blizniuk et al [33] reported that decayed teeth, missing teeth, papillary bleeding index, deep pocket depth, and the number of teeth present were factors associated with the perception oral status in 18–60-year-old adults in Belarus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, household income, dentures, the number of lost teeth, self-esteem, quality of life, stress level, sense of belonging, and level of depression are reportedly related to subjective OHS [32]. Blizniuk et al [33] reported that decayed teeth, missing teeth, papillary bleeding index, deep pocket depth, and the number of teeth present were factors associated with the perception oral status in 18–60-year-old adults in Belarus.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have proven self-rating of oral health to be a valid and reliable method for assessing OHS [29,30,31,32,33,34], which is considerably less expensive than a clinical examination. The current study indicated that Korean adults were able to assess their OHS accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Although efforts have been made to evaluate periodontal disease accurately through self‐reported measures, previous studies have shown some inconsistent results. In previous investigations, the questionnaire was used to investigate its ability to predict clinical periodontal disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent update from the American Academy of Periodontology indicated that the classification of periodontal disease should include evaluation of the following: (i) gingival attachment level; (ii) chronic versus aggressive periodontitis; and (iii) localised versus generalised periodontitis, with a focus on the percentage of affected teeth. The second method is a subjective measurement that identifies periodontal disease through self‐reported measures. In the objective measurement, severe periodontitis is defined as having one or more site(s) with a probing pocket depth ≥ 6 mm or clinical attachment loss (CAL) ≥ 5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐reported health measures are an efficient patient‐centred method used for identifying health outcomes, even for patients without prior health problems Patient‐reported data has been examined for usefulness in predicting illnesses, such as chronic obstructive pulmonary disease, diabetes mellitus, musculoskeletal pain, as well as healthcare utilisation. Further, the survey questions were taken from the BRFSS, a valid and frequently referenced self‐report survey used for chronic disease surveillance.…”
Section: Discussionmentioning
confidence: 99%